2017
DOI: 10.11114/jets.v5i4.2049
|View full text |Cite
|
Sign up to set email alerts
|

The African Guide: One Year Impact and Outcomes from the Implementation of a School Mental Health Literacy Curriculum Resource in Tanzania

Abstract: Despite the need for improving mental health literacy (MHL) among young people in low-and middle-income countries little research is available. Schools are an ideal location in which to address mental health literacy. A Canadian school-based mental health literacy resource was adapted for application in sub-Saharan Africa called the African Guide (AG). The AG is a classroom ready curriculum resource addressing all aspects of mental health literacy. Herein we provide teacher reported activity impacts and MHL ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
(15 reference statements)
2
25
0
1
Order By: Relevance
“…Moreover, a study conducted in South Africa revealed that 94% nurses were not able to correctly recognize various disorders, including schizophrenia (Dirwayi, 2002). Despite some of these concerning statistics, some work is being carried out on enhancing MHL in sub-Saharan Africa, with at least some partial success (e.g., Kutcher et al, 2015Kutcher et al, , 2017Kutcher et al, , 2019.…”
Section: Disorder Recognition: Depression and Schizophreniamentioning
confidence: 99%
“…Moreover, a study conducted in South Africa revealed that 94% nurses were not able to correctly recognize various disorders, including schizophrenia (Dirwayi, 2002). Despite some of these concerning statistics, some work is being carried out on enhancing MHL in sub-Saharan Africa, with at least some partial success (e.g., Kutcher et al, 2015Kutcher et al, , 2017Kutcher et al, , 2019.…”
Section: Disorder Recognition: Depression and Schizophreniamentioning
confidence: 99%
“…This includes, for instance, mental health literacy programs provided in specific schools for specific identified staff and/or students. For example, Kutcher, Wei [4] provided a three day mental health literacy training to 61 Tanzanian school teachers via their African Guide. Conversely, the second level at which mental health literacy development can occur is the public health level, which is broader and involves (b1) non-direct contact (e.g., via television and the internet) targeting (b2) the general public rather than specific individuals, via public health campaigns.…”
Section: Two Levels Of Mental Health Literacy Developmentmentioning
confidence: 99%
“…Teacher refresher training was conducted about 6 months following initial training. This intervention demonstrated positive impacts with significant, substantial, and sustained improvements in all aspects of teacher’s mental health literacy, including improved knowledge, decreased stigma, and enhanced help-seeking personally and for friends and family members (40) as well as the application of this resource into classroom settings with positive outcomes (41–43).…”
Section: School-based Approachesmentioning
confidence: 99%